SLC30 (ZnT) and SLC39 (ZIP) zinc transporter families: from gatekeepers of zinc homeostasis to promoters of tumorigenesis and targets for clinical therapy - Zhou, Yuqiao; Huang, Guangfa; Liu, Mengling; Zhang, Minghui; Wu, Bowen; Gu, Jinke (Frontiers in Immunology, 2026)
Zinc is a trace element that plays important functions in gene expression, enzymatic activity and cellular signaling. Cellular zinc homeostasis is tightly regulated by two solute carrier families: SLC30 (ZnT, zinc transporter) and SLC39 (ZIP, zrt- and irt-like protein), which are responsible for the efflux and influx of zinc respectively. Increasing evidence demonstrates that disturbed zinc homeostasis is involved in a variety of diseases, as the altered expression of zinc transporters usually remodels the tumor microenvironment and promotes malignant development. Here, we review the structural properties, tissue localization, and physiological functions of ZnT and ZIP transporters, with emphasis on digestive systems, immune systems, neurobiological systems, endocrine systems, and other systems. We focus on their pro-tumorigenic mechanisms in different cancers, including hepatocellular carcinoma, colorectal cancer, pancreatic cancer, gastric cancer, glioma, breast cancer, prostate cancer, as well as other cancers. Overall, the ZIP family is commonly upregulated in malignancies and promotes tumor development, through the activation of signaling pathways by zinc influx. The ZnT family exhibits more complex and context-dependent functions, performing tumor suppressive and tumor promoting effects simultaneously. Zinc transporters show great potential as diagnostic biomarkers and therapeutic targets, with many members displaying prognostic relevance. Translational development is progressing, with antibody-drug conjugates (ADCs) against ZIP6 and small molecule inhibitors targeting ZIP7 and ZIP8 entering preclinical and clinical trials. Future studies should focus on full-length structure analysis of zinc transporters (particularly ZIP members), their spatiotemporal dynamics and zinc signaling in the tumor microenvironment, and their roles in therapy resistance, all of which are important for developing precise targeting of zinc homeostasis in cancer treatment.